Implementasi Web Service dengan Metode Restful API dan QR Code untuk Aplikasi Manajemen Inventori pada Toko Indah Jaya Sport - Muhammad Iqbal Aulawi; Safrina Amini; Sri Mulyati (Asosiasi Pendidikan Tinggi Informatika dan Komputer Provinsi DKI Jakarta, 2022)
Information and telecommunications technology is currently experiencing rapid development that makes it easier for humans to carry out activities in many fields, one of which is the economic field. In carrying out its business, the Indah Jaya Sport store located in the Tangerang area is still recording the stock of goods manually. In addition, when the store staff wants to know the amount of stock available, it takes a long time, because they have to ask the warehouse first. This is what lies behind the creation of Web and Android-based inventory management applications using the RESTful API method. The RESTful method is used so that the two platforms are interconnected and integrated. This application consists of 2 applications, namely web applications and android applications. The web application is used to manage goods data which is also equipped with a QR Code generator where the generated QR Code can be printed and installed on the goods, then the QR Code can be scanned using the android application to find out the details of the item data. From the results of this study, it can be concluded that the inventory management application makes it easier for owners and staff to manage goods data and find out the amount of stock in the Indah Jaya Sport Store.